(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the worlds, and prayers and peace be upon our master Muhammad, the master of the prophets, and upon the God of the guides, his chosen companions, and those who are guided by his guidance until the Day of Judgment.